<h3>
♫ - - - - - - - - - - - - - - - ~Hello There!~ - - - - - - - - - - - - - - - ♫</h3>
➷ Just substitute the given value into anywhere you see the term x:
2 x 4^2 + 12
Follow the PEMDAS rule:
(calculate the exponential first)
4^2 = 16
Now we have:
2 x 16 + 12
(now the multiplication needs to be calculated)
16 x 2 = 32
Now we have:
32 + 12
Add them together to get the answer:
44 <== this is the answer
<h3><u>
✽</u></h3>
➶ Hope This Helps You!
➶ Good Luck (:
➶ Have A Great Day ^-^
↬ ʜᴀɴɴᴀʜ ♡
Answer:
Option D is the correct answer.
Step-by-step explanation:
Initial height = 4 feet
Given that the height of the tree increased by a constant amount each year for the next 6 years. At the end of the 6th year, the tree was 1/5th taller than it was at the end of the 4th year.
Let the rate of growing each year be g.
After 6 years height of tree = 4 + 6g
After 4 years height of tree = 4 + 4g
At the end of the 6th year, the tree was 1/5th taller than it was at the end of the 4th year.
That is
Option D is the correct answer.
Answer:
5/6
Step-by-step explanation:
1/6 + 1/6 = 2/6 TYPE A wood
1/4 + 1/4 = 2/4 TYPE B wood
2/6 + 2/4= ...
2/4 reduces to ?/2
That would be 1/2 because 4 divided by 2 is 2 & 2 divided by 2 is 1.
1/2= ?/6
Its 3/6 because we did 2 x 3 to get 6 and we do the same to the number 1. So we do 1 x 3 = 3
Now we have 3/6 + 2/6!
This is very easy now! We just do 2 + 3 which gets 5.
OUR ANSWER IS 5/6!! Hope this helps! plz mark as brainliest!
Answer
The answer and procedures of the exercise are attached in the following archives.
Step-by-step explanation:
You will find the procedures, formulas or necessary explanations in the archive attached below. If you have any question ask and I will aclare your doubts kindly.
3x(x²-5)
Multiply the bracket by 3x
(3x)(x^2)=3x^3
(3x)(-5)=15x
Answer: 3x^3+15x